RELATIONSHIP OF UNEMPLOYMENT AND POVERTY WITH CRIMES AGAINST PROPERTY: EVIDENCE FROM PAKISTAN - Mansoor Alam, Prof. Dr. Muqarrab Akbar (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Pakistan is going through its developmental phase and facing many challenges. This paper is based on one of the most critical issue is being faced by Pakistan since its inception is crimes against property. The research is all about the social evil of crime against property and there are two major causes of it unemployment and poverty, both these variables are analyzed in this paper and the significance level has been checked through correlation while the data has been collected from the jails of four provinces and capital territory of Pakistan specifically from the criminals involved in crimes against property and also from the investigation officers from police department of these particular crimes in shape of questionnaire which was constructed and distributed separately among the two different categories of respondents. In the end the key findings and conclusion are exactly according to the analysis which shows the significance of relationship between variables.